Portuguese Trade Unions and European Integration : Lessons from a Dual Vision - Costa, Hermes Augusto (2006)
Following the same course adopted towards the national issues, the positioning of the two main Portuguese trade union confederations (CGTP and UGT) vis-à-vis European integration also seems to lead to the adoption of distinct positions between them. Taking the “European challenge” as a backdrop, this paper attempts to systematize some of the most recent positions of the CGTP and UGT concerning European integration, taking into consideration not only the contributions to a Europeanization of union structures, but also the institutional evolution of the European Union.